Investigating the possibility of utilization of kaolin and the potential of metakaolin to produce green cement for construction purposes-A review - Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Liew, Y. M.; Mohd Mustafa Al Bakri, Abdullah; Luqman, Musa, Dr.; Khairul Nizar, I.; Heah, Cheng Yong (INSInet Publication, 2012)
Link to publisher's homepage at www.insipub.com/